Perspectives on the Disclosure of the Location of Goods in terms of Section 97 of the National Credit Act 34 of 2005 - Stéfan Renke; Corlia van Heerden (Obiter, 2021)
This article considers the provisions of section 97 of the National Credit Act 34 of 2005 (NCA), which are vitally important to credit providers and consumers alike and which entrench the obligation of a credit consumer who is subject to the Act to disclose to the credit provider the location of the goods financed under a credit agreement. Against a backdrop of similar provisions in the NCA’s predecessors (the Hire-Purchase Act 36 of 1942 and the Credit Agreements Act 75 of 1980), the article seeks to evaluate what changes, if any, the NCA has brought in this context and to make appropriate recommendations relating to the scope and application of section 97 of the NCA. The discussion of the disclosure measures in the NCA and its predecessors is preceded by a brief overview of the Acts’ fields of application insofar as the latter are relevant to the disclosure provisions. We conclude that the legislature needs to intervene and amend section 97 of the NCA (and regulation 34, which must be read with section 97), failing which these provisions will be a very limited tool in the hands of the credit provider to keep track of the goods that serve as security and their effectiveness will be greatly diminished.